Words Are Not for Hurting = Alfaz Takleef Denay Kay Liye Nahi Hotay - Verdick, Elizabeth; Illustrated by Heinlen, Marieka (Karachi Oxford University Press, 2016)
Encourages toddlers and preschoolers to express themselves using helpful, not hurtful, words. Includes a note for parents and caregivers.
The older children get, the more words they know and can use$1 (Bincluding hurtful words. This book teaches children that their words belong to them: They can think before they speak, then choose what to say and how to say it. It also explores positive ways to respond when others use unkind words and reinforces the importance of saying (3z(BI$1 (Bm sorry.(3y (BIncludes tips for parents and caregivers.s
Include Illustrations.
These books will help young children learn and practice basic social and emotional skills through real life situations and examples. Attractively illustrated, the stories are useful for teaching children in pre-primary and primary classes to behave responsibly and respectfully towards everyone. Each book includes a section for adults with discussion questions, games, activities, and tips that reinforce the skills and ideas being taught.
Keywords: Conversation -- Etiquette for children and teenagers -- Board books -- Pets